14-Noreudesmane sesquiterpenes from leaves of Nicotiana tabacum and their antiviral activity. (September 2016) - Shan-Zhai, Shang; Wei, Zhao; Jian-Guo, Tang; Jian-Xin, Pu; Dong-Lai, Zhu; Liu, Yang; Han-Dong, Sun; Guang-Yu, Yang; Yong-Kuan, Chen
Graphical abstract: Highlights: ⿢ Three new 14-noreudesmane sesquiterpenes were isolated from Nicotiana tabacum . ⿢ The structures of compounds were elucidated by spectroscopic methods. ⿢ Compound 1 exhibited moderate anti-TMV activity with inhibition rate of 46.7%. Abstract: Three new 14-noreudesmane sesquiterpenes (1 ⿿3 ) as well as four known ones (4 ⿿7 ) were isolated from the leaves of Nicotiana tabacum . Their structures were determined mainly by spectroscopic methods, including extensive 1D- and 2D NMR techniques. Compounds1⿿7 were evaluated for their anti-tobacco mosaic virus (anti-TMV) activities. The results showed that compound1 exhibited moderate anti-TMV activity with inhibition rate of 46.7%, which were higher than that of positive control (ningnanmycin).